Distribution patterns of Cuitlauzina pendula La Llave & Lex (Orchidaceae) over its phorophytes at the ‘Barranca de Cupatitzio’ National Park, in Uruapan, Michoacán, México - Pérez Decelis, Verónica A.; Gómez Alonso, Carlos; Ávila Díaz, Irene (Lankesteriana: International Journal on Orchidology, 2013)
.